Serological Characteristics of Pneumococci Isolated from Children with Acute Otitis Media in Sverdlovsk Region - V. . Romanenko; Y. . Beikin; A. . Somova; N. . Sbitneva; T. . Rozhkova (Эпидемиология и вакцинопрофилактика)
There are 22 - 25 thousand cases of Acute Otitis Media (AOM) registered annually in children < 14 years old in Sverdlovsk region. Average annual morbidity in 2009 - 2014 is 3748.5 ± 0.27 per 100 thousand children. In 2014 - 2015 non-interventional hospital-based surveillance study has been conducted in Sverdlovsk region establishing children ≤ 5 years old to be the leading risk group for AOM with 40.6% of cases caused by S. pneumoniae. Serotypes 3 (28.6%), 19F (17.2%), 14 (11.4%), 6А/В/С (11.4%) and 23F (5.7%) are playing the major role, that in total covers 77.1% of detected serotypes. S .pneumoniae serotypes coverage by pneumococcal conjugate vaccines is 54.2% for the 10-valent and 82.9% for the 13-valent.